An Investigation Into Pakistani Students’ Demotivation In Learning English: The Impact Of Resilience And Big-Five Personality Traits - Pathan, Zahid Hussain (2020)
The present research primarily aims at examining the L2 demotivation concept in relation to resilience and the big-five personality dimensions (i.e., conscientiousness, agreeableness, openness to experience, extraversion, and neuroticism). The present study adopted a sequential explanatory mixed methods research design to answer the proposed research questions.